2005
DOI: 10.1128/jcm.43.2.903-905.2005
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the E-Test Method for Detection of Colistin Resistance in Clinical Isolates of Acinetobacter baumannii

Abstract: We compared the E-test to the broth microdilution method for testing the susceptibility of 115 clinical isolates of Acinetobacter baumannii to colistin. Twenty-two (19.1%) strains were resistant to colistin and 93 (80.8%) strains were susceptible according to the reference broth microdilution method. A categorical agreement of 98.2% was found, with only two (1.7%) very major errors. Agreement within 1 twofold dilution between the E-test and the broth microdilution was 16.5%. Complete agreement was found for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 16 publications
4
63
1
4
Order By: Relevance
“…The observation of elevated pmr expression in patient 4's initial isolate led us to wonder if this isolate was in fact colistin resistant, despite demonstrating susceptibility by E-test. E-tests have been previously shown to be reliable indicators of colistin resistance in A. baumannii, demonstrating good correlation with other standard susceptibility tests (Arroyo et al 2005). Here, however, we found that despite susceptibility by E-test (MIC [minimal inhibitory concentration] = 0.125), broth-microdilution (BMD) experiments showed growth of PT4-S well into the range of colistin concentrations associated with resistance (MIC = 64 mg/mL) (Supplemental Table S4).…”
Section: Evolution Of a Baumannii Colistin Resistancementioning
confidence: 90%
“…The observation of elevated pmr expression in patient 4's initial isolate led us to wonder if this isolate was in fact colistin resistant, despite demonstrating susceptibility by E-test. E-tests have been previously shown to be reliable indicators of colistin resistance in A. baumannii, demonstrating good correlation with other standard susceptibility tests (Arroyo et al 2005). Here, however, we found that despite susceptibility by E-test (MIC [minimal inhibitory concentration] = 0.125), broth-microdilution (BMD) experiments showed growth of PT4-S well into the range of colistin concentrations associated with resistance (MIC = 64 mg/mL) (Supplemental Table S4).…”
Section: Evolution Of a Baumannii Colistin Resistancementioning
confidence: 90%
“…MICs of the CIP, GEN, PIP/tazobactam, CAZ and IMP were determined by E-test strip (Hi-Media) test as described by the manufacturer's instructions. MICs of the CLS were determined by E-test strip (Hi-Media) as described by the manufacturer's instructions and also by colistin sulfate (Sigma) broth dilution as described previously by Arroyo et al (2005). Isolates at least resistant to three classes of antibiotics were considered as MDR-AB as previously described by Manchanda et al (2010).…”
Section: Methodsmentioning
confidence: 99%
“…High error rates and low levels of reproducibility of the disk diffusion method for detecting colistin resistance are well documented (4), but Etest has shown excellent agreement with agar dilution (AD) and broth microdilution for testing colistin resistance in major Gram-negative bacteria (4)(5)(6). However, the performance of automated antimicrobial susceptibility testing systems has rarely been assessed in terms of determining colistin susceptibility in Acinetobacter species, especially for non-baumannii Acinetobacter strains (4,7).…”
mentioning
confidence: 99%